Migratory Attitudes as Specific Kind of Attitudes - S A Kuznetsova (Peoples' Friendship University of Russia (RUDN University), 2012)
The possibility of a migratory intentions research in the context of the social-psychological concepts of «attitude» and «social-psychological space» is proven in the article. The poly-object characteristic is proven as the specific feature of the migratory attitudes demanding social comparison.